A New Companion to the Libro de buen amor
1 online resource.
Keywords: The New Companion to the Libro de buen amor provides a platform for exploring current, innovative approaches to this classic poem. It is designed for specialists and non-specialists from a variety of fields, who are interested in investigating different aspects of Juan Ruiz's poem and developing fruitful new paths for future research. Chapters in the volume show how the book engages with Christian, Jewish and Muslim cultures, and delve into its legacy in the twentieth and twenty-first centuries. Part One sheds light on intersecting cultural milieux, from the Christian court of Castile, to the experience of Jewish and Muslim communities. Part Two illustrates how the poem's meaning through time can be elucidated using an array of theoretical and interdisciplinary approaches.